Respuesta :
3p^2 - 2p - 5
3p^2 -5p+3p-5 (5 times 3 equals 15)
p(3p-5) +1(3p-5)
Answer:
(3p - 5)(p + 1)
3p^2 -5p+3p-5 (5 times 3 equals 15)
p(3p-5) +1(3p-5)
Answer:
(3p - 5)(p + 1)
Answer:
factors (3p - 5) and (p + 1)
Step-by-step explanation:
The quadratic formula always "works" when you're looking to factor a quadratic expression or equation. Here, the coefficients are a = 3, b = -2 and c = -5. The discriminant is thus b²-4ac, which here is (-2)²-4(3)(-5), or 4+60, or 64. Because this discriminant is positive, we know that the quadratic has two real, unequal roots. These roots are:
-(-2)±√64 2 ± 8
p = ------------------- = --------------- = 10/6 and -1, or 5/3 and -1.
2(3) 6
These roots correspond to the factors (3p - 5) and (p + 1).